Narrative desire and the Book of Ruth - Powell, Stephanie Day (London Bloomsbury Publishing PLC, 2018)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Figures -- Acknowledgments -- Abbreviation -- Chapter 1 Narrative Desire and the Book of Ruth -- Introduction: âDo Not Press Me to Leave Youâ -- Finding Our Past -- Reading Desire -- Woman-Identified Hermeneutics -- Ruth and Its Interpretation -- Narrative Desire: Reading Ruth with Freud, Lacan, and Kristeva -- From Resistance to Re-engagement -- Chapter 2 Resistance: Ambiguity and Artistry in the Book of Ruth -- The Queer Traces of Ruth -- Queer Beginnings -- The Perversities of the Middle -- A Queer Future? -- Ambiguity and Desire -- Chapter 3 Rupture: Ruth and Fried Green Tomatoes -- Fried Green Appropriations -- Ambiguating Strategies -- The Power of âFriendsâ -- Intersecting Ambiguities -- The Heroine Disappears -- Historical Gleanings: A Diverse Community -- Chapter 4 Reclamation: Ruth and Oranges are not the Only Fruit -- You Say Tomato, I Say Orange: Reconfiguring Ruth -- From Origins to Exile -- From Exile to Return -- Not the Only Fruit: Ruth as Woman-Identified Daughter -- The Motherâs House -- Of Mothers, Demons, and Daughterhood -- Historical Gleanings: Finding Autonomy -- Chapter 5 Re-Engagement: Ruth and Golem, the Spirit of Exile -- Golem, the Spirit of Exile -- Love in Exile -- Losses Denied -- Heterosexual Melancholia, Redux -- Loss upon Loss -- Historical Gleanings: A History of Loss -- Chapter 6 Conclusion: (Un)Final Gleanings -- Returning to the Mother Text -- Bibliography -- Author Index -- Scripture Index -- Subject Index
Keywords: Electronic books